RECORDS OF TEN FRESHWATER OLIGOCHAETE SPECIES (ANNELIDA, CLITELLATA) FROM SUMATRA, JAVA AND KALIMANTAN, INDONESIA - Akifumi Ohtaka; Yoyok Sudarso; Linda Wulandari (BRIN Publishing (Penerbit BRIN), 2006)
Descriptions and taxonomic remarks are provided for ten species of freshwater oligochaetes (Annelida, Clitellata) from Sumatra, Java and Kalimantan, Indonesia. They include six naidines (Slavina appendiculata, Dero pectinata, Aulophorus hymanae, Branchiodrilus semperi, Pristina amphibiotica and P. osborni) and two tubificines (Limnodrilus claparedianus and L. grandisetosus) new to Indonesia. Enlarged ventral chaetae were described as an infraspecific variation in Pristina biserrata.